Implementasi Mesin Pemarut Kelapa dalam Upaya Pemberdayaan Masyarakat - Waluyo, Joko; Pratiwi, Yuli; Lestari, Nidi (DHARMA BAKTI, 2023)
Member of the dasa wisma group RT 06 Dusun Niten, Nogotirto, Kapanewon Gamping, Sleman  still grates the coconut manually, so the grated coconut yields 6 kg/hour. To increase the grated coconut with a larger capacity, the Dasa Wisma group needs a coconut grater machine. The AKPRIND Yogyakarta Institute of Science & Technology community service team provided training and handed over machine assistance to the dasa homestead group RT 06 Dusun Niten, Nogotirto, Kapanewon Gamping and provided training on how to operate and maintain coconut grater machines and how to store grated coconut properly. The purpose of this community service activity is to provide knowledge to the dasa wisma group RT 06 Dusun Niten, Nogotirto, Kapanewon Gamping how to operate, maintain the coconut grater machine, and store the grated coconut properly so that the machine lasts longer and the grated coconut doesn't rot, and the handover of a coconut shredding machine with a capacity of 40 kg / hour. Through this community service activity, it is hoped that Dasa Wisma Members and community members in RT 06, RW 12, Niten, Nogotirto Village, Gamping District, Sleman Regency can operate, maintain coconut shredding machines and be able to increase the production capacity of grated coconut by 800% when compared to using manual labor and can store grated coconut properly, so that it is expected to improve the community's economy. Community members positively assess and agree with this community service activity.